The Psychrotrophic Pseudomonas lundensis, a Non-aeruginosa Pseudomonad, Has a Type III Secretion System of the Ysc Family, Which Is Transcriptionally Active at 37°C - Ravi, Keerthikka; Falkowski, Nicole R.; Scales, Brittan S.; Akulava, Volha D.; Valentovich, Leonid N.; Huffnagle, Gary B. (mBio, 2022)
The type III secretion system (T3SS) is a needle-like structure found in Gram-negative pathogens that directly delivers virulence factors like toxins and effector molecules into eukaryotic cells. The T3SS is classified into different families according to the type of effector and host. Of these, the Ysc family T3SS, found in Yersinia species and Pseudomonas aeruginosa, confers high virulence to bacteria against eukaryotic hosts. Here, we present the first identification and transcriptional analyses of a Ysc T3SS in a non-aeruginosa Pseudomonas species, Pseudomonas lundensis, an environmental psychrotrophic bacterium and important agent of frozen food spoilage. We have identified and sequenced isolates of P. lundensis from three very distinct ecological niches (Antarctic temporary meltwater pond, U.S. supermarket 1% pasteurized milk, and cystic fibrosis lungs) and compared these to previously reported food spoilage isolates in Europe. In this paper, we show that strains of P. lundensis isolated from these diverse environments with ambient temperatures ranging from below freezing to 37°C all possess a Ysc family T3SS secretion system and a T3S effector, ExoU. Using in vitro and in vivo transcriptomics, we show that the T3SS in P. lundensis is transcriptionally active, is expressed more highly at mammalian body temperature (37°C) than 4°C, and has even higher expression levels when colonizing a host environment (mouse intestine). Thus, this Ysc T3SS-expressing psychrotrophic Pseudomonad has an even greater range of growth niches than previously appreciated, including diseased human airways. IMPORTANCE P. lundensis strains have been isolated from environments that are distinct and diverse in both nutrient availability and environmental pressures (cold food spoilage, Antarctic melt ponds, cystic fibrosis lungs). As a species, this bacterium can grow in diverse niches that markedly vary in available nutrients and temperature, and in our study, we show that these various strains share greater than 99% sequence ...